Narrative Analysis of Runway Incursion Reports in the National Transportation Safety Board Database To Identify Contributing. (December 2020) - Bhargava, Divya; Marais, Karen
A runway incursion occurs when an aircraft, ground vehicle, or a pedestrian is incorrectly present on the runway. This incorrect presence can lead to a collision resulting in fatal injuries and aircraft damage. Despite the aviation community's measures to reduce incursions, they continue increasing. Most runway incursions are a result of human error. Our limited knowledge of these human errors and their causes is hindering our ability to reduce runway incursions. While previous researchers have analyzed past runway incursions to identify types of human error, we still know little about the causes of these errors. The narratives in the NTSB database often provide detailed information to identify human errors and their causes. In this paper, we analyze the narratives of runway incursion reports in the NTSB database. We use task analysis to map human error to tasks they perform, and map the causes of these errors to the error itself.